Post-transjugular Intrahepatic Portosystemic Shunt Hepatic Encephalopathy: Sarcopenia Adds Insult to Injury - Puja Bhatia Kapoor,; Jaya Benjamin,; Harshita Tripathi,; Yashwant Patidar,; Rakhi Maiwall,; Guresh Kumar,; Yogendra Kumar Joshi,; Shiv Kumar Sarin, (Turkish Journal of Gastroenterology, 2023)
Background: Hepatic encephalopathy, which is a serious complication, and sarcopenia are undesirable consequences in cirrhosis. Transjugular intrahepatic portosystemic shunt increases the risk of hepatic encephalopathy. We investigated the effect of sarcopenia on the incidence of post-transjugular intrahepatic portosystemic shunt hepatic encephalopathy.Methods: Clinical data of patients who underwent transjugular intrahepatic portosystemic shunt were extracted retrospectively. Computed tomography images at L3 level of scans performed prior to transjugular intrahepatic portosystemic shunt were analyzed to assess skeletal muscle index—expressed as skeletal muscle area (cm2)/ height (m2).Results: Of 210 patients who underwent transjugular intrahepatic portosystemic shunt, complete information was available in 79 [male: 68 (86%); age: 50.5 ± 11.2 years; Child–Turcotte–Pugh score: 8.81 ± 1.23; etiology—alcohol: 44 (56%), non-alcoholic steatohepatitis: 16 (20%), others: 19 (24%); transjugular intrahepatic portosystemic shunt indication—ascites: 56 (71%); bleed: 23 (29%); sarcopenics: 42 (53%)]. Post-transjugular intrahepatic portosystemic shunt hepatic encephalopathy developed in 29 (37%) patients. In patients who developed hepatic encephalopathy, both serum ammonia [177.6 ± 82.5 vs. 115.5 ± 40.5 µg/dL, P =.008] and prevalence of sarcopenia [69% vs. 44%; P =.02; odds ratio (95% CI): 2.8 (1.08-7.4), P =.02] were higher, with sarcopenics having 3 times higher risk of hepatic encephalopathy and 8 times higher risk of multiple episode of hepatic encephalopathy [31% vs. 5.4%; odds ratio (95% CI): 8.2 (1.68- 40.5), P =.009]. In multivariate analysis, age [odds ratio (95% CI): 1.05 (1.001-1.11), P =.047], serum albumin [odds ratio (95% CI): 0.162 (0.05-0.56), P =.004], and skeletal muscle index [odds ratio (95% CI): 0.925 (0.89-0.99), P =.017] were independently associated with post-transjugular intrahepatic portosystemic shunt hepatic encephalopathy.Conclusions: Sarcopenia is present in nearly half of the cirrhotic patients undergoing transjugular intrahepatic portosystemic shunt, which increases the risk of a single episode of hepatic encephalopathy by 3-fold and that of multiple episodes of hepatic encephalopathy by 8-fold after transjugular intrahepatic portosystemic shunt procedure. Increased skeletal muscle index is associated with decreased risk of hepatic encephalopathy.Cite this article as: Bhatia Kapoor P, Benjamin J, Tripathi H, et al. Post-transjugular intrahepatic portosystemic shunt hepatic encephalopathy: Sarcopenia adds insult to injury. Turk J Gastroenterol. 2023;34(4):406-412.